Jailed Balloon Technique Is Superior to Jailed Wire Technique in Reducing the Rate of Side Branch Occlusion: Subgroup Analysis of the Conventional Versus Intentional StraTegy in Patients With High Risk PrEdiction of Side Branch OccLusion in Coronary Bifurcation InterVEntion Trial - Zhang, Dong; Zhao, Zhiyong; Gao, Guofeng; Xu, Han; Wang, Hao; Liu, Shuai; Yin, Dong; Feng, Lei; Zhu, Chenggang; Wang, Yang; Zhao, Yanyan; Yang, Yuejin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective: Jailed balloon technique (JBT) is an active side branch (SB) protection strategy and is considered to be superior to the jailed wire technique (JWT) in reducing SB occlusion. However, no randomized trials have proved that. We aim to investigate whether JBT could decrease the SB occlusion rate. Methods: CIT-RESOLVE (https://clinicaltrials.gov, NCT02644434, registered on December 31, 2015) is a randomized trial that assessed the effects of different strategies on SB occlusion rate in patients at high risk of SB occlusion. The present subgroup analysis enrolled bifurcation lesions (2.0mm ≤ reference vessel diameter of SB < 2.5mm) with V-RESOLVE score ≥ 12 points. The primary endpoint is SB occlusion. One-year clinical events were compared. Results: A total of 284 subjects at 16 sites were randomly assigned to the JBT group (n=143) or the JWT group (n=141). The rate of SB occlusion (9.1% vs. 19.9%, p=0.02) and periprocedural myocardial infarction (defined by World Health Organization [WHO], 7.0% vs. 14.9%, p=0.03) is significantly lower in JBT group than JWT group. JBT and JWT group showed no significant differences in cardiac death (0.7% vs. 0.7%, p=1.0), myocardial infarction (MI, 6.3% vs. 7.1%, p=0.79), target lesion revascularization (TLR, 1.4% vs. 2.1%, p=0.68), and major cardiac adverse events (MACE, a composite of all-cause death, MI, or TLR, 8.4% vs. 10.6%, p=0.52) during 1-year follow-up. Conclusions: In patients with high risk of SB occlusion (V-RESOLVE score ≥12 points), JBT is superior to JWT in reducing SB occlusion. However, no significant differences were detected in 1-year MACE.